Optimization of Lipase Catalyzed Synthesis of 3-O-benzoylbetulinic Acid - Yasin, Yamin (2004)
Betulinic acid derivatives were successfully synthesized from reactions of betulinic acid with benzoyl chloride and acetic anhydride using enzymes as biocatalyst in an organic solvent system. Preliminary detection of the reaction products were conducted using thin layer chromatography (TLC) and subsequent quantitative studies were conducted using gas chromatography. Characterizations of the products were further conducted using (NMR), (MS) and (FTIR). Initial screening of biological activities, revealed that the ester of the reaction of betulinic acid with benzoyl chloride showed a good cytotoxicity activity while no activity was detected for ester of reaction of betulinic acid and acetic anhydride. Thus, the reaction of betulinic acid and benzoyl chloride was chosen for further studies. Enzyme screening revealed that Novozyme was the most efficient biocatalyst for the reactions which produced a good yield of 3-O-benzoylbetulinic acid at 45.3%. The effects of various reaction parameters such as time of reaction, temperature, solvents used, amount of enzyme, mole ratio of substrates and initial water activity (aw) was studied to determine optimal condition of 3-O-benzoylbetulinic acid synthesis. The optimal conditions 3-O-benzoylbetulinic acid synthesis was obtained at incubation time of 12 h; temperature 50°C; mole ratio of betulinic acid/benzoyl chloride, 4.0; amount of lipase, 150 mg; organic solvent, chloroform and initial water activity (aw), 0.12. Response surface methodology (RSM) was then used to study the interactive effects of the reaction parameters. The best model for the reaction of 3-O-benzoylbetulinic acid was quadratic model. Generally, increasing both reaction temperature and amount of enzyme increased the percentage yields of products. However, a negative effect was detected at higher temperature due to denaturation of enzymes. Increasing reaction time and amount of enzyme improved the reactions, as did increasing reaction temperature and amount of enzyme. High amount of enzyme showed a slightly negative effect. In general, increasing the temperature and amount of enzyme resulted in negative effects of the response. Optimal conditions derived from the RSM differed slightly from those of the conventional “one-variable-at-a-time” approach due to the latter’s inability to consider interactions among the parameters. The percentage yield for the optimize reaction conditions derived from RSM was 48.5%. Betulinic acid and its acylated product were subjected to cytotoxicity, anti-viral, antimicrobe and anti-fungal assays in order to study the biological activities of this compound. The cytotoxicity evaluation of these compounds against cancer cell showed that 3-O-benzoylbetulinic acid from reaction of betulinic acid and benzoyl chloride (BCL) was the most active compound compared to betulinic acid (BA) and 3- acetylbetulinic acid (BAA). BCL showed IC50 <5 @g/ml which indicated significant cytotoxicity activity against all cancer cells. However, no activities were detected against dengue viral and some microbes and fungi that were tested.